Late Mesozoic rift evolution and crustal extension in the central Songliao Basin, northeastern China: Constraints from cross-section restoration and implications for lithospheric thinning - Ge, Rongfeng; Zhang, Q.; Wang, L.; Chen, J.; Xie, G.; Wang, X. (Taylor & Francis Inc., 2012)
The Songliao Basin, the largest oil-producing basin in China, was the centre of late Mesozoic rifting and lithospheric thinning in northeastern China. However, the rifts are still poorly revealed due to a thick cover of subsidence successions. By structural interpretation and sequential restoration of cross-sections based on new 2D seismic data and well data, this study presents the structural style, basin evolution, and horizontal crustal extension of the central Songliao Basin. We have developed a novel method to retrieve the regional extension principal strains. The results enable an assignment of rifting into two episodes. The earlier episode (ca. 157-130Ma) was dominated by distributed faulting of numerous planar normal faults trending NNE-SSW, NNW-SSE, or near NS, probably reflecting pre-existing basement fabrics; in contrast, the later episode (ca. 130-102Ma) was controlled by localized extension along several major listric faults. Horizontal crustal extension during rifting is estimated to have been 11-28km (10.6%-25.5%), with the long-term average rate varying from 0.20 to 0.51mm yr -1. Regional horizontal strains show a gradual evolution from biaxial extension at the beginning of rifting to WNW-ESE uniaxial stretching during the later rifting episode. Brittle crustal extension is interpreted to have been associated with vertical strain due to tectonic stretching, which is estimated to have contributed more in thinning the lower crust than the mantle lithosphere. Accordingly, a two-episode dynamic model is proposed to explain rifting in the Songliao Basin. We suggest that the earlier event was dominated by delamination of the thickened continental lithosphere, whereas the later event was probably controlled by regional crustal detachment due to slab subduction and stagnancy of the Izanagi lithospheric plate.